2017
DOI: 10.3390/ma10050500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermo-Oxidative Ageing on the Thermal and Dynamical Mechanical Properties of Long Glass Fibre-Reinforced Poly(Butylene Terephthalate) Composites Filled with DOPO

Abstract: In this work, the long glass fibre-reinforced poly(butylene terephthalate) (PBT) composites filled with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) were prepared by melt blending, and the influence of thermo-oxidative ageing on the static and dynamic mechanical properties, thermal behaviours and morphology of composites with different ageing time at 120 °C were investigated and analysed. The results showed that the mechanical properties decreased in the primary stage of ageing, while embrittlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The intensity of the aging conditions had a great influence on the mechanical properties of the composites. It has been reported that the tensile strength of long GF‐reinforced PBT with the addition of phosphorus‐based additive, 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide reduced in the beginning of the thermal‐oxidative aging process (10–40 days) and increased later on in the process (50–60 days). In another study on the thermo‐oxidative aging effect on mechanical properties of short CF /PA6 composites, the tensile strength of the CF /PA6 composites increased at the initial stage of aging (from 200 to 800 h of aging) and started to decrease thereafter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of the aging conditions had a great influence on the mechanical properties of the composites. It has been reported that the tensile strength of long GF‐reinforced PBT with the addition of phosphorus‐based additive, 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide reduced in the beginning of the thermal‐oxidative aging process (10–40 days) and increased later on in the process (50–60 days). In another study on the thermo‐oxidative aging effect on mechanical properties of short CF /PA6 composites, the tensile strength of the CF /PA6 composites increased at the initial stage of aging (from 200 to 800 h of aging) and started to decrease thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…This showed that the heat aging process damages the PBT structures and causes embrittlement within the composites. The reduction in the mechanical properties was mainly due to the degradation of the polymer matrix phase as well as the loosening of the filler–matrix interface adhesion after aged …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMA data for composites can provide the information about the storage modulus (G') and loss modulus (G'') of blends to give a better observation of the phase structure and interphase mixing of the blends [21,22]. Plots of the storage modulus (G') and loss modulus (G'') as a function of temperature for PA6/PNS blends with the frequency of 5 Hz are displayed in Figure 5 .…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…However, neat PBT can easily burn if ignited, with a peak of heat release rate up to 1404 kw/m 2 . A large amount of heat would be released in the combustion process, which would cause increased fire accident fatalness [ 2 ]. Therefore, the development of PBT composite with comprehensive mechanical properties, flame retardancy, and cost-effectiveness has become a key to expand PBT application.…”
Section: Introductionmentioning
confidence: 99%